Unit Link Application Quality Analysis Using ISO 25010 . Method (Case Study of PT Asuransi Jiwasraya Persero) - ulfa tunisa manu; Rina Noviana (Jurnal Ilmiah Matrik, 2022)
Abstract : PT Asuransi Jiwasraya Persero is a state-owned insurance company that is the largest local insurance company in Indonesia. PT Asuransi Jiwasraya has many products for individuals and groups. Jiwasraya's product management uses the Unit Link application, which is a web-based application that is used to facilitate the management of product transactions at Jiwasraya. Research on the analysis of Unit Link application quality aims to determine the quality of the application, using ISO 25010 which is a standard for software with eight characteristics, including functional suitability, performance efficiency, compatibility, usability, portability, and security. Determination of weights using the Analytical Hierarchy Process (AHP) method with the testing methods used are blackbox testing, questionnaires, observation and stress testing. The unit link application test got a score of 4.196 with a good category and the research results can help to determine the quality of the Unit Link application. Keywords: ISO 25010, Quality, Application, User Satisfaction, Unit Link